Historical evolution of human anthrax from occupational disease to potentially global threat as bioweapon. (December 2015) - D'Amelio, Enrico; Gentile, Bernardina; Lista, Florigio; D'Amelio, Raffaele
Abstract: Purpose: Anthrax is caused by Bacillus anthracis, which can naturally infect livestock, wildlife and occupationally exposed humans. However, for its resistance due to spore formation, ease of dissemination, persistence in the environment and high virulence, B. anthracis has been considered the most serious bioterrorism agent for a long time. During the last century anthrax evolved from limited natural disease to potentially global threat if used as bioweapon. Several factors may mitigate the consequences of an anthrax attack, including 1. the capability to promptly recognize and manage the illness and its public health consequences; 2. the limitation of secondary contamination risk through an appropriate decontamination; and 3. the evolution of genotyping methods (for microbes characterization at high resolution level) that can influence the course and/or focus of investigations, impacting the response of the government to an attack. Methods: A PubMed search has been done using the key words "bioterrorism anthrax". Results: Over one thousand papers have been screened and the most significant examined to present a comprehensive literature review in order to discuss the current knowledge and strategies in preparedness for a possible deliberate release of B. anthracis spores and to indicate the most current and complete documents in which to deepen. Conclusions: The comprehensive analysis of the two most relevant unnatural anthrax release events, Sverdlovsk in the former Soviet Union (1979) and the contaminated letters in the USA (2001), shows that inhalational anthrax may easily and cheaply be spread resulting in serious consequences. The damage caused by an anthrax attack can be limited if public health organization, first responders, researchers and investigators will be able to promptly manage anthrax cases and use new technologies for decontamination methods and in forensic microbiology. Highlights: Anthrax evolved from agricultural and occupational disease to threat as bioweapon Early infection recognition and management may mitigate anthrax attack consequences The review is intended to assist potential responders to face the anthrax threat